2020
DOI: 10.1002/pi.6153
|View full text |Cite
|
Sign up to set email alerts
|

Effects of epoxy resin crosslinking networks on stereocomplexation of poly(l‐lactic acid)/poly(d‐lactic acid) racemic blends

Abstract: In contrast to existing methods that add specific substances to poly(L-lactic acid)/poly(D-lactic acid) racemic blends to enhance stereocomplexation, in this study, a crosslinkable epoxy resin (EP) was introduced into a racemic blend. The results showed that, when the mass ratio of EP to racemic blend was 0.2:1 (EP:racemic blend = 0.2), regardless of the amount of diethylenetriamine (DETA) curing agent, homo-crystals in the racemic blend were essentially inhibited. With a fixed EP content, a 0.05:1 DETA to EP … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 76 publications
0
4
0
Order By: Relevance
“…One can find that the conformation transformation time (CTT) at T i near the melting point of HC (T m,H ) or T g is longer than that at T i around 120 °C (Figure 3e), which has been proven to be the fastest crystallization or nucleation temperature for PLA racemic blends with similar molecular weights. 10,24 Whether this is a coincidence or if there is a relationship between the structural evolutions of different scales requires further investigation. However, this was not the focus of this study.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…One can find that the conformation transformation time (CTT) at T i near the melting point of HC (T m,H ) or T g is longer than that at T i around 120 °C (Figure 3e), which has been proven to be the fastest crystallization or nucleation temperature for PLA racemic blends with similar molecular weights. 10,24 Whether this is a coincidence or if there is a relationship between the structural evolutions of different scales requires further investigation. However, this was not the focus of this study.…”
Section: Resultsmentioning
confidence: 99%
“…However, when PLA racemic blends with higher molecular weight crystallize below the melting point of HC, the growths of SC and HC compete. , There have been many efforts to regulate the content of SC in PLA racemic blends, including specific processing paths, chemical design of the PLA chains, and adding extra substances. Among them, the interaction between the PLA enantiomers is considered one of the most important factors for SC enhancement. Presently, the interaction between opposite enantiomers of other polymers is also considered as the driving force for their stereocomplexation .…”
Section: Introductionmentioning
confidence: 99%
“…PLA stereocomplex (scPLA) crystal formation subsequently grants higher melting temperature, 16 improved thermal resistance, 17 enhanced mechanical properties 18 and anti‐hydrolysis ability, 19 thus expanding the potential applications of PLA‐based materials 20–27 . It is found that the formation of stereocomplex crystals is selective and competitive, largely influenced by many parameters including molecular weight, 28,29 enantiomeric blending ratio, 30,31 preparation routes, 32,33 chain architectures 34 and the presence of additives 35,36 . While high molecular weight PLA confers greater mechanical properties, a low molecular weight is more conducive to encouraging stereocomplex crystallization to occur 37 …”
Section: Introductionmentioning
confidence: 99%
“…[20][21][22][23][24][25][26][27] It is found that the formation of stereocomplex crystals is selective and competitive, largely influenced by many parameters including molecular weight, 28,29 enantiomeric blending ratio, 30,31 preparation routes, 32,33 chain architectures 34 and the presence of additives. 35,36 While high molecular weight PLA confers greater mechanical properties, a low molecular weight is more conducive to encouraging stereocomplex crystallization to occur. 37 In recent years, a variety of star-shaped and branched PLAs have been reported, allowing an understanding about the effect of chain architecture on scPLA properties.…”
Section: Introductionmentioning
confidence: 99%